Complexities at the Au/ZrS3(001) interface probed by x-ray photoemission spectroscopy. (12th August 2021) - Dhingra, Archit; Lipatov, Alexey; Sinitskii, Alexander; Dowben, Peter A
Abstract: Interaction between the Au adlayers and ZrS3 (001) has been examined via x-ray photoemission spectroscopy (XPS). The angle-resolved XPS measurements reveal that ZrS3 (001) is disulfide (S2 2− ) terminated and the Au thickness-dependent XPS indicates that the observed band bending, for low Au coverage, is consistent with formation of a Schottky barrier at the Au/ZrS3 (001) interface. This band bending, however, appears to be suppressed as the thickness of Au adlayer is increased, indicating varying interfacial interactions at the Au/ZrS3 (001) interface. Such complex interface effects between Au and ZrS3 (001) may explain the observed non-ohmic I – V characteristics for a ZrS3 -based device, and could suppress current injection.